Adolescents’ maps about well-being, distress and selfdestructive trajectories: What’s in their voices? - Cruz, Diana (2017)
The mapping of adaptive and maladaptive trajectories in adolescence has been a key concern of developmental psychopathology research. Given the importance of studying adolescents’ own expert views of their experiences, we explored the factors that contribute to the adoption of trajectories characterized by well-being, by distress, and self-destructive trajectories, in a convenience sample of 33 community adolescents (13-21 years old) organized in five focus groups. Adolescents’ mapping of their own trajectories emerged through textual data analysis and was composed mainly of family and individual factors.We proposed a systemic hypothesis to explain how the interactivity between family and individual factors may foster different trajectories: family relational climate and parental emotional support create a context where self-regulation and positive self-esteem are increased. This study contributes to the deeper understanding of developmental trajectoriesand enriches reflections on the conceptualization and implementation of preventive and therapeutic interventions.